The Homotopy Analysis Method for Solving the Ratio-Dependent Predator-Prey System With Constant Effort Harvesting - Ebadi, Ghodrat; Rashedi, S.; Irandoust-Pakchin, S.; İnç, Mustafa (Southeast Asian Mathematical Soc-Seams, 2014)
In this paper, the homotopy analysis method ( HAM) is employed to approximate the solution of the ratio-dependent predator-prey system with constant effort harvesting. Numerical comparisons with the homotopy perturbation method (HPM), the Adomian decomposition method (ADM) and the Runge-Kutta (RK78) methods are presented. The HAM solutions contain the auxiliary parameters (h) over bar (1), (h) over bar (2), which provide us a simple way to adjust and control the convergence region of solution series.
Keywords: Homotopy analysis method; Ratio-dependent predator-prey system